Study on the relationship between the occurrence of landslide and the cracks at the edge of loess platform - Mingyu Wu; Xiujuan Yang (AIP Advances, 2022)
A landslide is a kind of geological disaster, which seriously threatens the production and lives of people around it. In collapsible loess areas, landslides occur more frequently. There are many cracks at the edge of the loess platform. This paper studies the relationship between the characteristics of cracks at the edge of the platform and the stability of the loess platform slope through numerical simulation. It is found that some cracks will eventually form a through sliding surface and form a landslide, while some cracks are relatively safe for the time being. According to the calculation results, the statistical formula is obtained to reveal the relationship between them, which is helpful to predict the loess platform landslide according to the cracks at the edge of the tableland in the future.